Vehiculation of methyl salicylate from microcapsules supported on textile matrix - Mendes, Samira (2021)
In recent years, textile industries have focused their attention on the development of functional finishing that presents durability and, consequently, controlled release. However, in the case of methyl salicylate microcapsules supported on a textile matrix, studies indicate only the interactions between substrate and microcapsules and the drug delivery system, not applying the release equations. This study reports the mechanism and kinetics of controlled release of microcapsules of gelatin and gum Arabic containing methyl salicylate as active ingredient incorporated into textile matrices. According to the results presented, it was possible to verify that the wall materials participated in the coacervation process, resulting in microcapsules with well-defined geometry, besides promoting the increase of the thermal stability of the active principle. The samples (100% cotton, CO, and 100% polyamide, PA) functionalized with microcapsules released methyl salicylate in a controlled manner, based on the adjustment made by the Korsmeyer–Peppas model, indicating a Fickian mechanism. The influence of temperature was noticeable when the samples were subjected to washing, since with higher temperature (50 °C), the release was more pronounced than when subjected to lower temperature (37 °C). The results presented in this study indicate that the mechanism of backbone release is influenced by the textile matrix and by the durability of the microcapsule during the wash cycles